Negative correlation of Modified Sperm Stress Test with Leukocyte in Sperm but not with the sperm concentration and motility - Dicky Moch Rizal; Geraldo Laurus; Nandia Septiyorini (Journal of Biomedicine and Translational Research, 2022)
Background: Sperm analysis is an initial detection procedure of male infertility recommended by the WHO. Sperm motility as one of the important parameters in sperm analysis has a close correlation with various determinants of male infertility and the success of Assissted Reproductive Technology (ART). Several laboratory assays were carried out as a complement to sperm analysis to describe the sperm ability for fertilization. One of the assays was the modified sperm stress test (MOST) to predict oocyte fertilization in In-Vitro Fertilization (IVF).Objective: This study aimed to assess the correlation between MOST ratio and sperm parameters in infertile men.Methods: This study is a descriptive-analytic study by taking sperm analysis and MOST data from 864 males with infertility problems who went to an infertility clinic, Sadewa IVF, Yogyakarta, Indonesia from May 2015 to November 2020.Results: The mean sperm volume and concentration of the 864 patients were 3.04 mL and 35.74 x 106 / mL respectively. The mean forward motility and normal morphology were 47.93% and 2.07% respectively. The mean leukocyte cell number was 0.84%, and the mean MOST ratio was 0.51. The results showed a positive correlation between sperm concentration (r = 0.235) and motility (r = 0.302) with the MOST ratio. Meanwhile, the leukocyte parameter negatively correlated with the MOST ratio (r = -0.076) and no correlation between other sperm parameters to the MOST ratio.Conclusion:There is a positive correlation between sperm concentration and motility with the MOST ratio, and a negative correlation between the number of leukocytes and the MOST ratio. This result supports the findings of previous studies regarding the importance of sperm motility examination in the success of ART. To the best of our knowledge, this is the first study to assess the MOST in male infertility patients with the big sample size.